2005
DOI: 10.1136/jmg.2004.024034
|View full text |Cite
|
Sign up to set email alerts
|

A PDGFRA promoter polymorphism, which disrupts the binding of ZNF148, is associated with primitive neuroectodermal tumours and ependymomas

Abstract: Background: Platelet derived growth factor receptor a (PDGFRa) expression is typical for a variety of brain tumours, while in normal adult brain PDGFRa expression is limited to a small number of neural progenitor cells. The molecular mechanisms responsible for the PDGFRa expression in tumours are not known, but in the absence of amplification, changes in transcriptional regulation might be an important factor in this process. Methods and results:We have investigated the link between single nucleotide polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…Other studies reported additional molecular changes, including increased expression of integrin α v β 3 in a high percentage of intracranial ependymomas, as well as expression of annexin A1 and cyclooxygenase 2 [21][22][23]. A single nucleotide polymorphism in the platelet-derived growth factor (PDGF) receptor-α gene promoter region in ependymomas has been reported, suggesting that the PDGF pathway may have a functional role in tumor biology [24].…”
Section: Molecular Pathway Abnormalitiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Other studies reported additional molecular changes, including increased expression of integrin α v β 3 in a high percentage of intracranial ependymomas, as well as expression of annexin A1 and cyclooxygenase 2 [21][22][23]. A single nucleotide polymorphism in the platelet-derived growth factor (PDGF) receptor-α gene promoter region in ependymomas has been reported, suggesting that the PDGF pathway may have a functional role in tumor biology [24].…”
Section: Molecular Pathway Abnormalitiesmentioning
confidence: 97%
“…Laboratory investigations suggest several potential therapeutic targets, including ErbB2 (Her2) and, in some cases, ErbB1 (EGFR) [20]. A polymorphism of the PDGRα gene promoter that causes dysregulation of this pathway was reported, suggesting that blocking this receptor may be a potential treatment strategy [24]. Similarly, overexpression of the α v β 3 integrin was found in a high percentage of ependymomas, and there now are specific agents targeting this integrin [21].…”
Section: Implications For Prognosis and Treatmentmentioning
confidence: 98%
“…However, rs3828610 of PDGFRB was not associated with PTC. Several researchers investigated the genetic association between polymorphisms of PDGFRA or PDGFRB and several diseases (16)(17)(18). Wu et al (16) reported that rs1800810 SNP of PDGFRA was associated with the severity and allergic status of childhood asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al (16) reported that rs1800810 SNP of PDGFRA was associated with the severity and allergic status of childhood asthma. De Bustos et al (17) revealed that a PDGFRA promoter polymorphism, which disrupts the binding of ZNF148, was associated with primitive neuroectodermal tumors and ependymomas. Kim et al (18) reported that the promoter SNPs (rs3756314, rs3756312 and rs3756311) of PDGFRB were associated with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…They also demonstrated that among the five promoter haplotypes, the H2 delta haplotype was unable to bind the transcription factor ZNF148. The role for ZNF148 in tumor development has yet to be elucidated, and the authors concluded that there may be a role for ZNF148/PDGFR-a in the development of ependymoma and PNET [38].…”
Section: The Pdgfr Alpha Pathwaymentioning
confidence: 96%